Pembrolizumab in Patients With Microsatellite Instability–High Advanced Endometrial Cancer: Results From the KEYNOTE-158 Study. Issue 7 (1st March 2022) - O'Malley, David M.; Bariani, Giovanni Mendonca; Cassier, Philippe A.; Marabelle, Aurelien; Hansen, Aaron R.; De Jesus Acosta, Ana; Miller, Wilson H.; Safra, Tamar; Italiano, Antoine; Mileshkin, Linda; Xu, Lei; Jin, Fan; et al.
Abstract : PURPOSE: Pembrolizumab demonstrated durable antitumor activity in patients with previously treated, advanced microsatellite instability–high or mismatch repair–deficient (MSI-H/dMMR) tumors, including endometrial cancer, in the nonrandomized, open-label, multicohort, phase II KEYNOTE-158 study (NCT02628067 ). We report efficacy and safety outcomes for patients with MSI-H/dMMR endometrial cancer enrolled in KEYNOTE-158. METHODS: Eligible patients from cohorts D (endometrial cancer, regardless of MSI-H/dMMR status) and K (any MSI-H/dMMR solid tumor, except colorectal) with previously treated, advanced MSI-H/dMMR endometrial cancer received pembrolizumab 200 mg once every 3 weeks for 35 cycles. The primary end point was objective response rate per RECIST version 1.1 by independent central radiologic review. Secondary end points included duration of response, progression-free survival, overall survival, and safety. RESULTS: As of October 5, 2020, 18 of 90 treated patients (20%) had completed 35 cycles of pembrolizumab and 52 (58%) had discontinued treatment. In the efficacy population (patients who received ≥ 1 dose of pembrolizumab and had ≥ 26 weeks of follow-up; N = 79), the median time from first dose to data cutoff was 42.6 (range, 6.4-56.1) months. The objective response rate was 48% (95% CI, 37 to 60), and median duration of response was not reached (2.9-49.7+ months). Median progression-free survival was 13.1 (95% CI, 4.3 to 34.4) months, and median overall survival was not reached (95% CI, 27.2 months to not reached). Among all treated patients, 76% had ≥ 1 treatment-related adverse event (grades 3-4, 12%). There were no fatal treatment-related events. Immune-mediated adverse events or infusion reactions occurred in 28% of patients (grades 3-4, 7%; no fatal events). CONCLUSION: Pembrolizumab demonstrated robust and durable antitumor activity and encouraging survival outcomes with manageable toxicity in patients with previously treated, advanced MSI-H/dMMR endometrial cancer.